Characterisation of polar unresolved complex mixtures in groundwater associated with weathered petroleum - Lang, Dale Allan (Curtin University, 2011)
Polar unresolved complex mixtures (UCMs) associated with weathered petroleum in groundwater have received little attention in the literature. These compounds can be incorporated in analytical techniques that are commonly used to measure the level of petroleum contamination in groundwater, such as total petroleum hydrocarbon (TPH) analyses. Distinguishing between polar compounds associated with weathered petroleum and natural organic matter (NOM) can be difficult, and may lead to TPH concentrations in groundwater that are not representative of the actual level of petroleum contamination. This thesis provides a detailed study of the dissolution, accumulation and formation of polar UCMs associated with weathered diesel. Novel techniques for differentiating polar UCMs sourced from petroleum and NOM were also developed.Chapter 2 identifies the presence of polar UCMs in groundwater associated with weathered diesel. A polar compound (1-adamantanol) that can only be sourced from petroleum was identified suggesting the polar UCMs were derived from petroleum and not NOM. In Chapters 3 and 4, the formation, accumulation and dissolution of polar UCMs and related compounds from the biodegradation of petroleum were studied. These compounds were shown to accumulate in the weathered diesels and partition strongly into water (up to 96 mg/L) resulting in a similar polar contamination to that observed in the groundwater associated with weathered diesel in Chapter 2. Comparisons of the polar compounds identified in weathered diesel and associated groundwater were used to suggest where the polar compounds (and polar UCMs) form and accumulate (i.e. within the groundwater or the soil profile).These accumulation and dissolution processes for polar UCMs associated with weathered petroleum were suggested to be an ongoing source of persistent petroleum contamination and a potential risk to the environment and human health that can be misidentified or overlooked as NOM.In Chapters 5 and 6, novel techniques for differentiating polar UCMs from petroleum and NOM in TPH were developed. The technique developed in Chapter 5 differentiates polar UCMs present in TPH based on the differences in the carbon skeletons of petroleum and NOM. The technique applies a dehydrogenation reaction to reduce the complexity and compound types present in polar UCMs by defunctionalising and aromatising polar compounds into predominately hydrocarbons. Application of the technique to environmental samples containing polar UCMs from petroleum and NOM (some containing no identifiable hydrocarbons or polar compounds) showed the technique can be used to distinguish the sources of polar UCMs. The formation of diamondoid reaction products with carbon skeletons that can only be sourced from petroleum provided the most significant evidence for differentiating NOM and petroleum.The reaction products formed from petroleum polar UCMs also provided insight into the composition and formation of polar UCMs associated with weathered diesel. In Chapter 6, a simple screening tool was developed to allow the rapid assessment of the likely sources (NOM or petroleum) of polar UCMs present in surface water and groundwater. Assessment of the likely sources was based on differences in the TPH and TOC characteristics of NOM and petroleum polar UCMs.